2021
DOI: 10.3390/ijms22179216
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Angiogenesis Factors in Hypoxic Diabetic Wound Conditions by siRNA Delivery: Additive Effect of LbL-Gold Nanocarriers and Desloratadine-Induced Lysosomal Escape

Abstract: Impaired wound healing in people with diabetes has multifactorial causes, with insufficient neovascularization being one of the most important. Hypoxia-inducible factor-1 (HIF-1) plays a central role in the hypoxia-induced response by activating angiogenesis factors. As its activity is under precise regulatory control of prolyl-hydroxylase domain 2 (PHD-2), downregulation of PHD-2 by small interfering RNA (siRNA) could stabilize HIF-1α and, therefore, upregulate the expression of pro-angiogenic factors as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“… 133 PHD2 siRNA LbL AuNPs in vitro NIH-3T3 mouse fibroblasts in vivo increased levels of VEGF and FGF-2 accelerated migration and proliferation of NIH3T3cells Shaabani et al. 134 FKBPL siRNA RALA NPs in electrospun ALG/PVA-CHT/PVA nanofiber in vitro human microvascular endothelial cells in vivo C57BL/6J mice 5-mm full-thickness wounds in vitro improved cell migration increased endothelial tubule formation in vivo increased in angiogenesis increased blood vessel density Mulholland et al. 135 PHD2 plasmid shRNA FuGENE transfection reagent in vitro fibroblasts of diabetic Lepr db/db mice in vivo female diabetic Lepr db/db mice full-thickness 6-mm wounds on the dorsa of diabetic mice accelerated wound healing increased vascular density upregulation of SDF-1, VEGFα, PDGFα, and CD31 improved perfusion increased survival of muscle bulk Paik et al.…”
Section: Gene-silencing-based Therapeutics For Wound Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“… 133 PHD2 siRNA LbL AuNPs in vitro NIH-3T3 mouse fibroblasts in vivo increased levels of VEGF and FGF-2 accelerated migration and proliferation of NIH3T3cells Shaabani et al. 134 FKBPL siRNA RALA NPs in electrospun ALG/PVA-CHT/PVA nanofiber in vitro human microvascular endothelial cells in vivo C57BL/6J mice 5-mm full-thickness wounds in vitro improved cell migration increased endothelial tubule formation in vivo increased in angiogenesis increased blood vessel density Mulholland et al. 135 PHD2 plasmid shRNA FuGENE transfection reagent in vitro fibroblasts of diabetic Lepr db/db mice in vivo female diabetic Lepr db/db mice full-thickness 6-mm wounds on the dorsa of diabetic mice accelerated wound healing increased vascular density upregulation of SDF-1, VEGFα, PDGFα, and CD31 improved perfusion increased survival of muscle bulk Paik et al.…”
Section: Gene-silencing-based Therapeutics For Wound Angiogenesismentioning
confidence: 99%
“…In this nanoformulation, siRNA was electrostatically complexed with chitosan-coated gold NPs, after which a final outer layer of chitosan (AuNPs@CS) or poly L-arginine (AuNPs@PLA) was coated around NPs for the protection of siRNA and to facilitate and tune the endosomal escape process ( Figure 9 A). 134 It was found that AuNPs@PLA not only has outstanding stability over time as a siRNA carrier but also proved to be highly effective for cytosolic release after endocytic uptake. In addition, the combination of those nanocarriers with the cationic amphiphilic drug desloratadine resulted in an augmented endosomal escape of siRNA for AuNPs@PLA, while this was not the case for AuNP@CS.…”
Section: Gene-silencing-based Therapeutics For Wound Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…124 Currently, the NPs that deliver siRNAs to promote wound management are composed of lipids, polymers (eg, chitosan, PEG), hyperbranched cationic polysaccharides (HCP), and silicon. [125][126][127][128][129][130] Shaabani et al developed layer-by-layer self-assembled siRNA-loaded gold NPs with two different outer layers -Chitosan (AuNP@CS) and Poly L-arginine (AuNP@PLA). 126 They compared the two types of NPs, which had a similar core structure.…”
Section: Gene Deliverymentioning
confidence: 99%
“…[125][126][127][128][129][130] Shaabani et al developed layer-by-layer self-assembled siRNA-loaded gold NPs with two different outer layers -Chitosan (AuNP@CS) and Poly L-arginine (AuNP@PLA). 126 They compared the two types of NPs, which had a similar core structure. They found that the two polymers had different escape mechanisms: the buffering capacity of chitosan resulted in endosome disruption, 131 while PLA bound to the endosome lipid bilayer and promoted escaped through pore formation.…”
Section: Gene Deliverymentioning
confidence: 99%